Model characteristics of technicaland tactical actions of highly qualified taekwondoists as a basis for the development of control measures - Pshenichnikov , P.; Mitova , O. (Sportyvnyi Visnyk Prydniprovia, 2025)
Introduction. The study presents an analysis of competitive performance of winners of international ranking taekwondo (WTF) tournaments with the aim of developing models of technical and tactical indicators, taking into account the features of individual fighting styles. These models are intended to serve as a foundation for forming a system of tools for monitoring technical and tactical preparedness of highly qualified taekwondo athletes, based on modeling competitive activity during the training process. It is emphasized that an important instrument for planning and managing the training process is the development of training and control programs for technical and tactical preparedness based on modeling the competitive activity of leading athletes in the chosen sport. It has been established that in combat sports as well as in team sports, practical schemes for managing the training of top class athletes are developed according to the «strongest athlete model» concept. It has also been determined that, depending on the type of combat sport and the qualification level of athletes, the number of typical fighting styles varies. Purpose of the study – to develop model characteristics of indicators and generalized models of effective technical and tactical actions of highly qualified taekwondo athletes during competitive activity, considering the features of individual fighting styles. Methods of the study: theoretical analysis and generalization of scientific and methodological literature (sources were studied in accordance with the research problem); analysis of documentary materials (competition protocols were analyzed); system analysis (used to ensure a logical and consistent approach to the organization and acquisition of research results); chronological method (it enabled the study of sources reflecting the sense of the research process from the beginning up to the end of competitions); modeling method (it was applied to construct generalized models of technical and tactical actions of qualified taekwondo athletes depending on their fighting style); and methods of mathematical statistics (used to calculate total and average values of indicators and their effectiveness). Results of the study. In order to forecast athletic performance and design training and control programs for technical and tactical preparedness based on modeling competitive activity of high class taekwondo athletes, regularities of competitive performance have been studied. The most significant quantitative and qualitative model characteristics of individual fighting styles in WTF taekwondo were identified. Four variants of model characteristics and four generalized models of effective technical and tactical actions of qualified taekwondo athletes were developed, in accordance with main fighting styles: game style, tempo style, power style, and tactical style. Conclusions. It was found that for comprehensive monitoring of the technical and tactical preparedness of highly qualified taekwondo athletes, it is necessary to establish a system of control tools, including control exercises and control bouts based on modeling the competitive activity of world-leading athletes. Quantitative indicators that can serve as a basis for developing such a control system within the training process, using the «competition day model» were identified. It was noted that the frequency of effective use of particular kicks is not a constant value; all taekwondo actions during a match vary depending on the opponent’s personality and tactics. This fact diminishes the relevance of coaches, athletes and researchers’ focusing solely on quantitative and qualitative indicators, highlighting the importance of integrated preparedness factors. Therefore, the significance of the «result control» element increases, where the monitoring of quantitative and qualitative indicators of generalized models of leading taekwondo athletes with different individual fighting styles is not the main control objective but rather a condition for performing tasks during control exercises and control bouts.